Contacts with general practitioners, dentists, and medical specialists among nursing home residents: a cross-sectional study in 44 German nursing homes - Jonas Czwikla; Annika Schmidt; Maike Schulz; Ansgar Gerhardus; Guido Schmiemann; Karin Wolf-Ostermann; Daniel Gand; Anna-Carina Friedrich; Falk Hoffmann; Heinz Rothgang (BMC, 2022)
Abstract Background Nursing home residents have high medical care needs. Their medical care utilization is, however, lower compared to community-dwelling elderly and varies widely among nursing homes. This study quantified the utilization of general practitioners (GPs), dentists, and medical specialists among nursing homes and residents, and investigated whether dentist utilization is associated with individual and nursing home characteristics. Methods Forty-four nursing homes invited 2124 residents to participate in a cross-sectional study. For 10 medical specialties, data on contacts in nursing homes, practices, and by telephone in the last 12 months were assessed at individual and nursing home level. The proportion of nursing homes and residents with any form of contact, and the median number and interquartile range (IQR) of contacts among individuals with contact were determined. Using multilevel logistic regression, associations between the probability of individual dental care utilization and sex, age, LTC grade, years of residence, sponsorship, number of nursing home beds, and transport and medical escort services for consultations at a practice were investigated. Results The proportion of nursing homes with any form of contact with physicians ranged from 100% for GPs, dentists, and urologists to 76.7% for gynecologists and orthopedists. Among the nursing homes, 442 residents participated (20.8% response). The proportion of residents with any contact varied from 97.8% for GPs, 38.5% for neurologists/psychiatrists, and 32.3% for dentists to 3.0% for gynecologists. Only for GPs, neurologists/psychiatrists, dentists, otorhinolaryngologists, urologists, and dermatologists, the proportion was higher for nursing home contacts than for practice and telephone contacts. Among residents with any contact, the median number of contacts was highest for GPs (11.0 [IQR 7.0-16.0]), urologists (4.0 [IQR 2.0-7.0]), and neurologists/psychiatrists (3.0 [IQR 2.0-5.0]). Dentist utilization varied widely among nursing homes (median odds ratio 2.5) and was associated with higher age. Conclusions Almost all residents had regular contact to GPs, but only one third had contact with dentists. Lower proportions with contact were found for medical specialists, except for neurologists/psychiatrists. Reasons for the large variations in dental care utilization among nursing homes should be identified. Trial registration DRKS00012383 [2017/12/06].